Illegal trade in wildlife vertebrate species in the West Bank, Palestine - Elias N. Handal (Elsevier, 2021)
A total of 79 species of local vertebrates (birds, mammals, and reptiles) are found to be in illegal trade in the West Bank, Palestine, during 2013–2020. Data were collected from visits to the animal markets in the main cities of the West Bank (Bethlehem, Hebron, Jenin, Jericho, Nablus, Ramallah, and Salfit) and from advertisements in social media. Birds were the most traded animals represented in 59 species (74.7%), followed by 12 species of reptiles (15.2%) and eight species of mammals (10.1%). Nineteen species are listed under CITES appendices (17 birds and 2 mammals under appendixes II and III, respectively). As for the conservation status according to the IUCN Red List, two bird species (Streptopelia turtur and Serinus syriacus) and one reptile (Testudo graeca) are listed as VU, while two mammals (Hyaena hyaena and Gazella gazella) are listed as NT and EN, respectively. Based on the local status, three species of bird are considered critically endangered (Coturnix coturnix, Asio flammeus, and Aquila chrysaetos), one bird is endangered (Falco subbuteo), and two mammals (Hyaena hyaena and Gazella gazella) are considered endangered and vulnerable respectively. This study reveals the urgent need to control animal trade in the Palestinian Territories.